The Effect of Nano Technology Liquid Organic Fertilizer on The Growth of Red Spinach (Amaranthus tricolor L.) Cultivated Hydroponic - Fadilla Sonia Putri; Resti Fevria; Des M; Irma Leilani Eka Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Hydroponic cultivation with a wick system is one of the techniques used to increase the production of red spinach (Amaranthus tricolor L.). One of the weaknesses of hydroponics is the appearance of nutrient deposition. To reduce nutrient deposition in the wick system, it is necessary to apply nanotechnology to break down particles in the growth media and nutrients used so that the particles become smaller and are absorbed by plants more easily. Reduces precipitation in the wick system. This research was conducted using the RAL method (completely randomized design) which consisted of 6 treatments and 4 replications namely Control (Well Water + 100% AB Mix), P1 (Nano Technology Water + 100% AB Mix), P2 (Nano Technology Water + 25% POC+75% AB Mix), P3 (nano technology water+50% POC+50% AB Mix), P4 (nano technology water+75% POC+25% AB Mix), P5 (nano technology water+100% POC). The data obtained were analyzed with variance (ANOVA) followed by the DMRT test at 5% level. The results of this study were that the use of liquid organic fertilizer with nano technology had an effect on the growth of red spinach plants, this was seen in the highest plant in P4 with a plant height of 37.20 cm with the highest average number of leaves. at P4. Control and P1 with 28 leaves, the highest average leaf surface area was 19.95 cm2 in P3, the highest average wet weight was 2.85 g in the control, the highest average dry weight was in P1. 0.67g.